Isolated Tricuspid Valve Surgery for Functional Tricuspid Regurgitation - Kaneyuki, Daisuke; Jordan, Andrew M.; Rosen, Jake L.; Macmillan, Thomas Reese; Morris, Rohinton J.; Tchantchaleishvili, Vakhtang (The Thoracic and Cardiovascular Surgeon, 2024)
Background Severe tricuspid regurgitation (TR) adversely affects long-term survival; however, isolated tricuspid valve (TV) surgery has been rarely performed due to high operative mortality. In addition, the previous literature included heterogeneous TR etiologies. Therefore, we aimed to elucidate early and long-term outcomes of isolated TV surgery for functional TR.Methods An electronic search was performed to identify all relevant studies. Baseline characteristics, perioperative variables, and clinical outcomes were extracted and pooled for meta-analysis.Results This meta-analysis included seven studies. Pooled analyses showed that 68% (35, 89) of patients had preoperative atrial fibrillation or flutter, and 58% (11, 94) had a history of left-sided valve surgery. Seventy-three percent (65, 80) of patients had at least one physical exam finding of right-sided heart failure, and 57% (44, 69) were in New York Heart Association class III or IV. TV replacement was more common than repair. In TV replacement, bioprosthetic valve (39%, 13, 74) was more common than mechanical prosthesis (22%, 18, 26). The early mortality rate was 7%. Twenty percent of patients required a permanent pacemaker postoperatively. The overall 1- and 5-year survival rates were 84.5 and 69.1%, respectively.Conclusion More than half of the patients who underwent isolated TV surgery for functional TR had undergone left-sided valve surgery and had significant heart failure symptoms at the time of surgery. Further studies on the surgical indication for concomitant TV surgery at the time of left-sided valve surgery and the appropriate timing of surgery for isolated functional TR are needed to improve survival.
Keywords: cardiac; heart valve surgery; tricuspid valve